A astronomia observacional no ensino médio integral: uma proposta para o ensino de física - Azevedo Filho, Janilson Simões de (2025)
Since ancient times, sky observation has fascinated various civilizations, bringing together philosophical, historical, and scientific perspectives. However, observational astronomy in basic education faces challenges, such as teacher training and the lack of accessible materials. This research aimed to develop, implement, and evaluate an educational product based on hands-on activities for teaching physics through observational astronomy. Inspired by the principles of Paulo Freire and the methodology of the Three Pedagogical Moments, the material includes activities that follow the stages of problematization, knowledge organization, and practical application, involving sky observation and promoting a guided experience of celestial phenomena. The product was implemented in a second-year full-time high school class, with the participation of 25 students. Data were collected through questionnaires, which revealed elements that demonstrated how the approach of sky observation through practical activities fostered student engagement, stimulated epistemological curiosity, and connected physics concepts with everyday elements. It is expected that the educational product will contribute to new feasible astronomy teaching practices, strengthening the learning of scientific concepts as well as the development of critical and observational skills through practical activities.